"Great Grandmother Mary Bemister Forward's Brother, Hon. John Bemister" - Rorke Family (1875)
Hon. John G. Bemister (1815-1892), eldest son of William Willis Bemister and Ann (Howell) Bemister, was born at Carbonear on 23 April 1815. He married Jane Taylor at Carbonear on 3 January 1839, and had six children. John was the brother of Capt. Willis Bemister, William Bemister, Mary (Bemister) Forward and Sarah Jane (Bemister) Pike. He was also an uncle of Ernest Edward Forward and great-uncle of Kathleen (Forward) Rorke. John died at Harbour Grace on 19 December 1892. The Rorke Family Photograph Collection contains 301 black and white and 28 colour photographs of the Rorke Family of Carbonear, Newfoundland, as well as the Forward and Bemister families from that area who are linked to it by marriage. Although spanning from the 1840s-1970s, most photos are from 1900-45, showing family events, homes and Newfoundland and Labrador locations. There is also an album of photos taken while James Rorke attended the Leys School in Cambridge, England.